Don't Mention the War! Second World War Remembrance and Support for European Cooperation - de Vries, Catherine (Wiley, 2019)
The notion that through increased state cooperation and dependency, national divisions can be overcome and peace can be secured, is at the core of European integration. Political elites often refer to the devastations of the Second World War (WWII) as a way to convey the added value of European cooperation today. Do references to the devastations of WWII enhance public support for European cooperation today? By presenting evidence from survey experiments conducted in the six largest member states (France, Germany, Italy, Poland, Spain and the Great Britain) in July 2017, this study suggest that they do, albeit only when it comes to financial assistance for other member states in dire economic need. References to the devastations of WWII do not make respondents more willing to support free movement of people or the establishment of a European army. These findings suggest that reminding people of the devastations of WWII triggers a largely transactional response among the public: a willingness to provide financial support, but nothing more. This evidence suggests that securing public support for free movement of people or European security cooperation through historical rhetoric might be difficult to achieve.
Keywords: public opinion; historical narratives; European integration; survey experiments; 59 Ciencia Política; ODS 10 - Reducción de las desigualdades